Platelet-rich plasma injection for acute Achilles tendon rupture: two-year follow-up of the PATH-2 randomized, placebo-controlled, superiority trial. (1st November 2022) - Keene, David J.; Alsousou, Joseph; Harrison, Paul; O'Connor, Heather M.; Wagland, Susan; Dutton, Susan J.; Hulley, Philippa; Lamb, Sarah E.; Willett, Keith; ,
Abstract : Aims: To determine whether platelet-rich plasma (PRP) injection improves outcomes two years after acute Achilles tendon rupture. Methods: A randomized multicentre two-arm parallel-group, participant- and assessor-blinded superiority trial was undertaken. Recruitment commenced on 28 July 2015 and two-year follow-up was completed in 21 October 2019. Participants were 230 adults aged 18 years and over, with acute Achilles tendon rupture managed with non-surgical treatment from 19 UK hospitals. Exclusions were insertion or musculotendinous junction injuries, major leg injury or deformity, diabetes, platelet or haematological disorder, medication with systemic corticosteroids, anticoagulation therapy treatment, and other contraindicating conditions. Participants were randomized via a central online system 1:1 to PRP or placebo injection. The main outcome measure was Achilles Tendon Rupture Score (ATRS) at two years via postal questionnaire. Other outcomes were pain, recovery goal attainment, and quality of life. Analysis was by intention-to-treat. Results: A total of 230 participants were randomized, 114 to PRP and 116 to placebo. Two-year questionnaires were sent to 216 participants who completed a six-month questionnaire. Overall, 182/216 participants (84%) completed the two-year questionnaire. Participants were aged a mean of 46 years (SD 13.0) and 25% were female (57/230). The majority of participants received the allocated intervention (219/229, 96%). Mean ATRS scores at two years were 82.2 (SD 18.3) in the PRP group (n = 85) and 83.8 (SD 16.0) in the placebo group (n = 92). There was no evidence of a difference in the ATRS at two years (adjusted mean difference -0.752, 95% confidence interval -5.523 to 4.020; p = 0.757) or in other secondary outcomes, and there were no re-ruptures between 24 weeks and two years. Conclusion: PRP injection did not improve patient-reported function or quality of life two years after acute Achilles tendon rupture compared with placebo. The evidence from this study indicates that PRP offers no patient benefit in the longer term for patients with acute Achilles tendon rupture. Cite this article: Bone Joint J  2022;104-B(11):1256–1265.